Age changes in muscles’ tension in individuals with greater phisical efficiency - Drozdowski, Sławomir (Anthropological Review, 1974)
Changes' examination which you may observe in hardness of arm's triceps (m. triceps brachii), biceps (m. biceps brachii) and calf's gastrocnemius (m. gastrocnemius), was this paper's purpose. This researches have respect to right extremities of individuals with greater phisical efficiency. It was taken account of 611 male and 281 female.Muscle's hardness measurements were performed using W. Szulakowskis — Z. Drozdowski's tonometr. Collected material is divided into age groups (annual) from 22 to 29 years and 30-, 35-, 40-years old groups. Data are preparing on account of statistics.These measurements allow us to ascertain following stamps: the smallest muscle's hardness characterizes the triceps of arm, than biceps of arm and the greatest hardness has calf's gastrocnemius muscle. Hardness of researched muscles is dependent upon the individual's age and it shows the decrescent tendency. Numerical value of muscles’ hardness fall is various. This is worth to emphasize the feminine groups characterizes greater changes. Masculine individuals all groups of age you may observe greater muscles’ hardness than in feminine individuals.